2020
DOI: 10.1016/j.cytogfr.2020.06.001
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection: The role of cytokines in COVID-19 disease

Abstract: COVID-19 disease, caused by infection with SARS-CoV-2, is related to a series of physiopathological mechanisms that mobilize a wide variety of biomolecules, mainly immunological in nature. In the most severe cases, the prognosis can be markedly worsened by the hyperproduction of mainly proinflammatory cytokines, such as IL-1, IL-6, IL-12, IFN-γ, and TNF-α, preferentially targeting lung tissue. This study reviews published data on alterations in the expression of different cytokines in patients with COVID-19 wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
899
9
27

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 995 publications
(1,039 citation statements)
references
References 180 publications
37
899
9
27
Order By: Relevance
“…This is consistent with increased disease progression when COVID-19 patients were stratified based on age. A previous study found that peripheral VEGF concentrations were significantly higher in COVID-19 patients than in healthy controls (81). We also find this effect in our human samples ( Figure 8B) where people with COVID-19 that are older than 60 years of age have more VEGF protein in their peripheral blood.…”
Section: Neutrophil Degranulation and Ifn Pathways Overlap Between Cosupporting
confidence: 82%
“…This is consistent with increased disease progression when COVID-19 patients were stratified based on age. A previous study found that peripheral VEGF concentrations were significantly higher in COVID-19 patients than in healthy controls (81). We also find this effect in our human samples ( Figure 8B) where people with COVID-19 that are older than 60 years of age have more VEGF protein in their peripheral blood.…”
Section: Neutrophil Degranulation and Ifn Pathways Overlap Between Cosupporting
confidence: 82%
“…Secondly, acute in ammation caused by SARS-CoV-2 might alter lipid metabolism as well. Severe and critical patients with COVID-19 were commonly accompanied with largely excessive release of proin ammatory cytokines, such as IL-1, IL-6, IL-12, IFN -γ and TNF-α, as the disease progressed over time and gradually got worse [30]. It was shown that tumor necrosis TNF-α, IL-1β, and IL-6 could decrease synthesis and/or secretion of apolipoproteins in hepatic cell lines in dose-dependent way [31].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no clinical and experimental studies on the protective effect of HDL and Apo-AI in COVID-19. In severe and critical COVID-19 patients, clinical outcome can be signi cantly worsened by excessive release of pro-in ammatory cytokines [30]. HDL and Apo-AI may help in preventing in ammatory injury and improving the clinical outcome with anti-in ammatory and antioxidative properties.…”
Section: Discussionmentioning
confidence: 99%
“…We next determined if SARS-CoV-2 infection of K18 hACE2 transgenic mice resulted in a cytokine storm, as described during the development of severe COVID-19 disease in humans (reviewed in [22][23][24][25][26] ). Multiple tissues were analyzed to define local and systemic inflammatory, TH1, TH17, and TH2 responses.…”
Section: Sars-cov-2 Infection Of K18 Hace2 Transgenic Mice Drives a Lmentioning
confidence: 99%